490 Immunotherapy (IT) Training in Canada: Perspectives of Fellows-in-training on the First Immunotherapy Training Manual - Pun, Teresa (World Allergy Organization Journal, 2012)
BACKGROUND: Allergen immunotherapy (IT) is a key component of allergy practice, however fellows state that there is inadequate IT exposure during their training. In response, the Canadian Society of Allergy and Clinical Immunology (CSACI) unveiled the first ever IT Training Manual for fellows-in-training at the annual 2010 CSACI meeting. The manual was distributed during a faculty-led teaching session. This was a pilot investigation to determine the perspectives of fellows in training about the IT training manual. METHODS: Canadian fellows-in-training in Allergy and Clinical Immunology (list derived from CSACI) were contacted via email to complete a survey (using survey monkey), both quantitative (Likert scales) and qualitative, to assess their opinion on the faculty-led session on IT and the IT Training Manual. RESULTS: Sixty-nine Canadian fellows-in-training were invited to complete the survey and 16 (23%). Fifty-four percent of 13 respondents were in their first year of fellowship. Seven respondents (58% of 12 respondents) attended the 2010 CSACI fellow-in-training session and received the IT Training Manual. One respondent commented that it was “more information than we've had in all of our fellowship!” The same 7 respondents “somewhat liked” or “liked” the large group format, but felt that the experience could be improved in the future with the addition of cased-based learning in smaller groups. One respondent commented that “as in intro, it was good in a larger setting.” All 7 respondents felt that their understanding of IT was positively impacted by the faculty-led session. Eighty-six percent of 7 respondents indicated that the Training Manual “somewhat impacted” to “very much impacted” their understanding of IT. One commenter stated that “it is the basis of my knowledge thus far.” Most respondents (86%) preferred the current paper booklet format of the IT Training Manual. CONCLUSIONS: The results of this pilot survey demonstrate that some fellows-in-training found the faculty-led session on IT and the IT Training Manual useful. Future studies will help to further elucidate the utility of these 2 educational interventions.